Application of Guided Inquiry Learning Model to Cognitive Competencies of Students Assisted by Mind Map in Senior High School UNP Laboratory Development - Nia Anggraini; Ramadhan Sumarmin; Ardi Ardi; Elsa Yuniarti (ATRIUM PENDIDIKAN BIOLOGI, 2019)
Research on the effect of mind-assisted mind inquiry models on students' knowledge competencies in SMA X-class UNP Laboratory Development Cross-interest. Guided Inquiry learning models assisted by Mind Map if both are combined students can understand learning material more clearly so that students can improve their learning competencies and can develop students' critical thinking skills. This study uses quasi experiments. And research design Randomized Control-Group Pretest-Posttest Design sampling technique is done by purposive sampling. The instrument used to measure the results of cognitive learning competencies of students using objective tests. The results showed that there were differences in cognitive learning outcomes from the mind map assisted guided inquiry model that had a positive effect than the direct learning model.